KARAKTERISTIK DAYA PANEL SURYA POLYCRYSTALLINE 100 WP TERHADAP PERUBAHAN TEMPERATUR: KARAKTERISTIK DAYA PANEL SURYA POLYCRYSTALLINE 100 WP TERHADAP PERUBAHAN TEMPERATUR - Teguh Yuwono Teguh (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2022)
Energy and Mineral Resources Ministry's 2018 Electricity Statistics data shows that the installed capacity of Solar Power Plants (PLTS) only reaches 0.09 percent of the national generating capacity. This means that if the national generating capacity in 2018 reaches 64.92 gigawatts (GW), then PLTS only has a share of around 58.43 megawatts (MW). This value is very small considering the potential for solar energy in Indonesia can reach 207 GW. The majority of power plants in Indonesia are still dominated by PLTU which reaches 42.34 percent or around 27.49 GW. In testing the characteristics of solar panels, the method used is to install prototype materials and equipment for 100 WP Polycristalline solar panels and collect data through direct measurements. The method of observation is to collect data related to temperature variations that are happening at certain times and conditions that can affect the size of the power. The equipment used for this measurement includes: a thermometer used to measure temperature, a Charge Controller Module (SCC) as a control for charging the battery as well as measuring the amount of DC electricity that is always displayed, a camera for documenting the measurement results, a battery as a store of electrical power and a dc wattmeter as a measurement tool. the amount of electricity from the solar penel as well as connecting cables and other auxiliary equipment. The results of this study include: the pattern of power characteristics on a Pollycrystalline 100 WP solar panel at a temperature of 25˚C to a temperature of 39˚C is directly proportional to temperature, with a minimum value of 2.7 Watt at a temperature of 25˚C until it reaches a maximum power of 28, 5 Watt when the temperature reaches 39 C, the SUNSIA brand of Pollycrystalline 100 WP solar panel can produce effective electrical energy when the temperature is above 34 C, from the power generated by the solar panel to charge a 12 V 32A battery with an initial voltage of 5.1 Volts until it reaches a voltage of 13.8 Volts takes 8 hours.